Analysis of risk factors associated with complications after laparoscopic gastric bypass in patients with obesity - Nevmerzhytskyi, V. O.; Tsiura, Y. P. (General Surgery, 2025)
Global data indicate that complications after laparoscopic gastric bypass occur in 5.8 to 12.4% of patients. Recent studies identify prior abdominal surgeries, chronic liver diseases, arterial hypertension, chronic lung diseases, and repeated bariatric procedures as primary risk factors for postoperative complications. Objective – to determine the primary risk factors associated with complications in obese patients after laparoscopic gastric bypass. Materials and methods. A retrospective analysis was conducted on data from 556 obese patients, as defined by IFSO criteria, who underwent laparoscopic gastric bypass surgery between 2011 and 2025 at the Department of General Surgery No 2, Bogomolets National Medical University. Of these patients, 261 (46.3%) were men and 295 (53.7%) were women. The mean body weight was 151.88 (95% CI: 135.5 – 168.1) kg, and the mean body mass index was 46.73 (95% CI: 43.93 – 49.52) kg/m2. The surgical and anesthetic risk, assessed using the ASA scale, was 3.42 (95% CI: 3.31 – 3.53). Two groups of patients were established: a control group (2011 – 2019) and an experimental group (2019 – 2024), to evaluate the impact of the new strategy on the incidence of complications. Results. Univariate logistic regression analysis identified seven factors with a significance level of <0.1: duration of surgery, postoperative pain level, early mobilization, chronic obstructive pulmonary disease, gastroesophageal reflux disease, sleep apnea, and diabetes mellitus. To determine the minimum set of factorial features associated with the occurrence of complications in obese patients after laparoscopic gastric bypass, a multivariate logistic regression analysis was employed. This analysis identified five factorial features associated with complication risk: «duration of surgery», «postoperative pain level», «delayed mobilization», «sleep apnea syndrome», and «diabetes mellitus». Conclusions. The factors influencing the development of postoperative complications in obese patients after laparoscopic gastric bypass surgery included the duration of surgery, postoperative pain level, delayed mobilization, sleep apnea syndrome, and diabetes mellitus.